Architecture of 54 moist-forest tree species: traits, trade-offs, and functional groups - Poorter, L; Bongers, L; Bongers, F (Ecology (Durham), 2006)
Tree architecture is an important determinant of the height extension, light capture, and mechanical stability of trees, and it allows species to exploit the vertical height gradient in the forest canopy and horizontal light gradients at the forest floor. Tropical tree species partition these gradients through variation in adult stature (Hmax) and light demand. In this study we compare 22 architectural traits for 54 Bolivian moist-forest tree species. We evaluate how architectural traits related to Hmax vary with tree size, and we present a conceptual scheme in which we combine the two axes into four different functional groups. Interspecific correlations between architecture and Hmax varied strongly from negative to positive, depending on the reference sizes used. Stem height was positively related to Hmax at larger reference diameters (14-80 cm). Species height vs. diameter curves often flattened toward their upper ends in association with reproductive maturity for species of all sizes. Thus, adult understory trees were typically shorter than similar-diameter juveniles of larger species. Crown area was negatively correlated with Hmax at small reference heights and positively correlated at larger reference heights (15-34 m). Wide crowns allow the small understory species to intercept light over a large area at the expense of a reduced height growth. Crown length was negatively correlated with Hmax at intermediate reference heights (4-14 m). A long crown enables small understory species to maximize light interception in a light-limited environment. Light-demanding species were characterized by orthotropic stems and branches, large leaves, and a monolayer leaf arrangement. They realized an efficient height growth through the formation of narrow and shallow crowns. Light demand turned out to be a much stronger predictor of tree architecture than Hmax, probably because of the relatively low, open, and semi-evergreen canopy at the research site. The existence of four functional groups (shade-tolerant, partial-shade-tolerant, and long- and short-lived pioneer) was confirmed by the principal component and discriminant analysis. Both light demand and Hmax capture the major variation in functional traits found among tropical rain forest tree species, and the two-way classification scheme provides a straightforward model to understand niche differentiation in tropical forests.